2021
DOI: 10.2478/acph-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Potential of germanium-based compounds in coronavirus infection

Abstract: The first germanium compounds which exhibited immunomodulatory and antiviral effects were sesquioxane-type germanates. To date, more than a dozen compounds containing germanium have been synthesized and are being actively studied. They include germanium carboxylates and citrates, complexes of germanium with resveratrol, daphnetin, mangiferin, chrysin, quercetin, ascorbic and nicotinic acids, amino acids, gamma-lactones, germanium-containing spirulina, yeast and others. Germanium-based compounds have shown the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 62 publications
1
12
0
2
Order By: Relevance
“…Therefore, THGP may effectively inhibit the cytokine storm during SARS-CoV-2 infection by suppressing inflammasome activity. Several authors have noted that Ge-132 may prevent aggravation of COVID-19 induced by anti-oxidative stress and immune activation [ 32 , 33 ]. It has been also reported that Ge-132 suppresses influenza virus growth and reduces mouse mortality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, THGP may effectively inhibit the cytokine storm during SARS-CoV-2 infection by suppressing inflammasome activity. Several authors have noted that Ge-132 may prevent aggravation of COVID-19 induced by anti-oxidative stress and immune activation [ 32 , 33 ]. It has been also reported that Ge-132 suppresses influenza virus growth and reduces mouse mortality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the field only began to intensively develop in the 1970s, when the first water-soluble organic germanium compounds were synthesized, gaining attention due to their wide range of biological activities. This topic has been addressed in several reviews [1,5,6,8,24,[36][37][38][39][40][41][42][43][44] as well as a monograph [7].…”
Section: Of 19mentioning
confidence: 99%
“…The results of the research once again confirmed the complete safety of Ge-132. The comprehensive study of the various biological activities of Ge-132 [8], including those previously known [36], in particular antitumor [83][84][85][86][87][88][89] and immunomodulating [43,52,54,90], also continued.…”
Section: Germanium Sesquioxidesmentioning
confidence: 99%
See 2 more Smart Citations